Transnational Environmental Crime in the Context of International Criminal Law and Victim-Centered Environmental Justice - Zico Junius Fernando; Firdaus Arifin; Muhamad Adystia Sunggara; Fardana Kusumah (Lampung Journal of International Law, 2025)
Transnational environmental crimes are among the most complex and destructive forms of cross-border criminality, including wildlife trafficking, illegal trade of endangered species, transboundary pollution, and unlawful exploitation of natural resources by state and non-state actors. These offenses have yet to gain explicit recognition as core international crimes, despite their severe impacts on ecosystems, geopolitical stability, and local communities. This article examines the urgent need to incorporate transnational environmental crimes into international criminal law and emphasizes a victim-centered environmental justice approach to restore the rights and sustainability of affected communities. Using normative and comparative legal analysis, it advocates recognizing ecocide and cross-border environmental offenses as serious violations of ecological justice and human rights. The study further explores how victim protection frameworks can extend to Indigenous communities, future generations, and non-human entities, offering guidance for Indonesia in building a more responsive, transnational, and victim-oriented environmental criminal justice system.